Visceral obesity is not correlated with lymph node metastases nor colorectal cancer survival - Melo, Vanessa (2019)
Introduction: The presence of lymph node metastasis in colorectal cancer is determinant for prognosis and for treatment planning. The relationship between visceral fat and the prognosis is not fully documented in the literature, so this study intended to evaluate whether there is a relationship between the presence of visceral obesity and the presence of lymph node metastases and the prognosis of patients with colorectal cancer. Materials and methods: A sample of 68 patients who underwent surgery for colorectal cancer at Hospital de Braga between 1/1/2007 and 31/12/2007 was constructed, and their clinical and pathological data were recorded. Visceral fat, subcutaneous, and total fat areas were measured on preoperative computed tomography. Visceral obesity was defined as a ratio of visceral fat to total fat area >0.29. The ratio of metastatic lymph node (; number of metastatic lymph node/number of lymph node examined) was calculated. Results: There was a significant association between visceral obesity and male sex (p = 0.032). Patient survival at 5 and 10 years of follow-up was higher in patients with subcutaneous obesity in both periods, but not significant. There was a significant association between the ratio of metastatic lymph node and survival at 5 and 10 years (p = 0.03 and p = 0.002, respectively), with higher survival when ratio of metastatic lymph node = 0% and worse for ≥ 18%. Conclusion: In this study, no significant association was observed between visceral obesity and the number of metastatic lymph node, nor with survival at 5 and 10 years.